Pengaruh Current Ratio, Return On Assets, dan Nilai Tukar Rupiah terhadap Harga Saham Farmasi - Neni Nur'aeni; Gusganda Suria Manda (Universitas Bina Sarana Informatika, 2021)
This research was conducted at manufacturing companies in the consumer goods industry sector. This research focus is on the pharmaceutical company sector listed on the Indonesia Stock Exchange (IDX) in 2014-2018. The population in this study was 11 companies. This study used a purposive sampling method, and then, based on the predetermined CRiteria, obtained eight samples of companies that will be tested in this study. The type of data in this research is quantitative data. The data source used is secondary data sourced from the official website of the IDX, BI, and their respective companies. This study's results indicate that only the Current Ratio and Return On Assets partially have a significant effect on stock prices. However, simultaneously Current Ratio, Return On Assets, and Rupiah Exchange Rate have a significant influence on stock prices.